New Deal (National Archives, 2016)
Links to web sites relating to the New Deal era useful for research on New Deal agriculture, labor, and arts programs. The New Deal , Painting/Mural by Conrad A. Albrizio. Dedicated to President Roosevelt. Placed in the auditorium of the Leonardo Da Vinci Art School, 149 East 34th Street, New York, New York,& ca. 1934 (FDR Presidential Library NLR-PHOCO-A-59333) Contents NARA Resources Other Resources NARA Resources "Archival Vintages for The Grapes of Wrath" Daniel Nealand's Prologue article shows how John Steinbeck used WPA documentary source material provided by Thomas E.
Keywords: _open access

Herbert Hoover Papers - Anonymous (The Herbert Hoover Presidential Library and Museum, 2017)
The papers of Herbert Hoover had been accumulating since 1919 at the Hoover Institution on War, Revolution, and Peace at Stanford University. In 1960 Hoover decided to donate materials beginning with his time as Secretary of Commerce onwards to the Herbert Hoover Presidential Library. The papers are arranged into five groups. Hoover Papers [accordion classes="" id="903" expand_first="false"][/accordion]
Keywords: _open access

Historical Statistical Abstracts of the US - US Census Bureau (Census.gov)
Comprehensive summary of statistics on the social, political and economic conditions of the United States from 1878 to 2012.
Keywords: _open access

Women Working, 1800-1930 (CURIOSity Digital Collections)
An exploration of women's impact on the economic life of the United States between 1800 and the Great Depression.
Keywords: _open access